OPTIMASI TITIK INTERKONEKSI DISTRIBUTED GENER-ATION (PLTM MUARA) GUNA MEMINIMALKAN RUGI – RUGI DAYA MENGGUNAKAN METODE ARTIFICIAL BEE COLONY (ABC) PADA PENYULANG PANJI - I Made Arya Supartana; Rukmi Sari Hartati; I Wayan Sukerayasa (Program Studi Teknik Elektro UNUD, 2018)
Distributed Generation (DG) is a small power plant that can increase realibility, voltage profil, and reduce power losses in distribution network. DG interconnection locations that are less suitable can in/crease power losses. A possibility that can be done to reduce these power losses is by optimizing DG interconnection points. Optimization of the DG interconnection points on the feeder of Panji aims to minimize power losses, where the initial power losses occur at 48.2 kW. Optimization technique is using the Artificial Bee Colony (ABC) method with losses after simulation at 32.263 kW. When compared with the conditions before and after optimization there is a differ-ence in power losses of 16.035 kW, to a decrease in power losses of 33.2% from the previous loss.